2018
DOI: 10.1002/mnfr.201800446
|View full text |Cite
|
Sign up to set email alerts
|

Sulfated Polysaccharide from Sea Cucumber and its Depolymerized Derivative Prevent Obesity in Association with Modification of Gut Microbiota in High‐Fat Diet‐Fed Mice

Abstract: Scope Sulfated polysaccharide from sea cucumber (SCSP), Stichopus japonicus, has been shown to prevent diverse diseases, but little is known about its effects on obesity and gut microbiota in mice fed a high‐fat diet (HFD). Methods and results Diet‐induced obese, BALB/c mice are fed an HFD with or without SCSP and depolymerized SCSP (d‐SCSP, 0.004 kcal g−1) for 8 weeks. The results show that both SCSP and d‐SCSP reduce body weight, fat and liver hypertrophy, insulin resistance, and serum lipid and inflammatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
120
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(132 citation statements)
references
References 45 publications
(74 reference statements)
11
120
1
Order By: Relevance
“…At the genus level, our results reflected that the relative abundances of Bifidobacterium, Bacteroides, Alistipes, Lachnospiraceae NK4A136 group and Alloprevotella decreased while that of Parabacteroides, Eubacterium xylanophilum group, GCA-900066575, Lachnoclostridium, Lachnospiraceae UCG-006 and Romboutsia increased in the HFD group compared with the control group. In line with our results, earlier studies found that the abundances of Bifidobacterium (Zhu et al, 2018), Bacteroides (Zhang et al, 2015;Martinez et al, 2017), Alistipes (Zhu et al, 2018), Lachnospiraceae NK4A136 group , and Alloprevotella were negatively correlated with obesity, and the abundances of Parabacteroides (Lieber et al, 2018;Zhao et al, 2018), Eubacterium xylanophilum group , GCA-900066575 , Lachnoclostridium (Zhao et al, 2017b), Lachnospiraceae UCG-006 (Kang et al, 2019), and Romboutsia (Zhao et al, 2018) were positively correlated with obesity. Bifidobacterium, a beneficial microbial species, producing lactic acid and acetic acid, can reduce intestinal pH and inhibit the growth of various detrimental bacteria to maintain intestinal health (Wang R. et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…At the genus level, our results reflected that the relative abundances of Bifidobacterium, Bacteroides, Alistipes, Lachnospiraceae NK4A136 group and Alloprevotella decreased while that of Parabacteroides, Eubacterium xylanophilum group, GCA-900066575, Lachnoclostridium, Lachnospiraceae UCG-006 and Romboutsia increased in the HFD group compared with the control group. In line with our results, earlier studies found that the abundances of Bifidobacterium (Zhu et al, 2018), Bacteroides (Zhang et al, 2015;Martinez et al, 2017), Alistipes (Zhu et al, 2018), Lachnospiraceae NK4A136 group , and Alloprevotella were negatively correlated with obesity, and the abundances of Parabacteroides (Lieber et al, 2018;Zhao et al, 2018), Eubacterium xylanophilum group , GCA-900066575 , Lachnoclostridium (Zhao et al, 2017b), Lachnospiraceae UCG-006 (Kang et al, 2019), and Romboutsia (Zhao et al, 2018) were positively correlated with obesity. Bifidobacterium, a beneficial microbial species, producing lactic acid and acetic acid, can reduce intestinal pH and inhibit the growth of various detrimental bacteria to maintain intestinal health (Wang R. et al, 2018).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, these changes of microbial composition influenced by butyrate have significant functional implications as indicated in Spearman correlation analysis (Figure S4). The above‐mentioned genera are highly correlated with expression levels of lipid and/or glucose metabolic genes, which is in agreement with earlier findings showing their involvement in lipid/glucose metabolism (Martínez et al, ; Wang et al, ; Zhu et al, ). Microbiota‐derived metabolite TMAO was reported to profoundly modulate atherosclerosis by impairing RCT and inducing the formation of foam cells (Koeth et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…[ 62 ] Another study reported that HFD increased the abundance of LPS‐producing Proteobacteria and decreased the abundance of Tenericutes that are positively related to the content of short‐chain fatty acids (SCFAs). [ 63 ] Interestingly, the supplementation of LCP or Vc can effectively reduce the abundances of Firmicutes and Proteobacteria and increase the abundances of Bacteroidetes and Tenericutes in the gut of the HFD‐fed rats, which may result in an increase in the content of SCFAs. Lactobacillus , butyric acid‐producing Ruminococcus , and Clostridium , which are related to oxidative stress and inflammation, [ 64 ] are beneficial intestinal bacteria.…”
Section: Discussionmentioning
confidence: 99%